“Perceiving myself small: a body volume regression to age three” — a new manifestation of Alice in Wonderland Syndrome in a migraine patient - Valença, Marcelo Moraes; Reis, Rita Santana dos; Andrade, Juliana Ramos de (Headache Medicine, 2025)
IntroductionAlice in Wonderland Syndrome (AIWS) is a rare neurological condition often associated with migraine and characterized by perceptual distortions of body image, time, and space.Case reportWe report the case of a 33-year-old woman with a history of migraine since adolescence who presented with recurrent episodes of AIWS. During severe migraine attacks, she experienced microsomatognosia, perceiving her body as shrinking to the size of a child when her eyes were closed, along with temporal  distortion described as “slow motion” of her surroundings. Neurological examination, brain MRI, and angiography were unremarkable. Despite prophylactic therapy with topiramate and acute treatment with triptans, disabling attacks persisted.ConclusionThis case highlights the complex relationship between migraine and AIWS, reinforcing the need for clinicians to recognize AIWS manifestations as part of the migraine spectrum. Early identification can prevent misdiagnosis and improve patient management.